The role of high knee range of motion at discharge on functional outcome after total knee arthroplasty: a retrospective cohort study - Jimin Ma; Yakun Zhu; Zhen Dong; Ziming Guo; Rui Song; Wendan Cheng (BMC Musculoskeletal Disorders)
Abstract Background The study aimed to investigate the impact of high knee range of motion at discharge on functional outcome after total knee arthroplasty (TKA). Methods We conducted a retrospective study of 136 patients with primary osteoarthritis who were treated between January 2022 and June 2023. Patients were classified according to the type of rehabilitation program: high range of motion (HROM) group or control group. In the HROM group, patients underwent high-intensity rehabilitation, especially without restricting the range of motion (ROM) following knee surgery. In the control group, patients received routine rehabilitation, with the affected knee achieving approximately 90 degrees of flexion at discharge. Patients’ data related to postoperative knee ROM, Hospital for Special Surgery (HSS) score, visual analogue scale (VAS) score, transfusion rate, wound complications, thrombus of lower limb, and usage of analgesic drugs were recorded to assess the influence of ROM at discharge on clinical outcomes. Results The HROM group had a higher knee ROM compared to the control group at discharge (P < 0.001). There were no significant differences between the HROM group and the control group in the basic demographic information, hospital stay and operation time (P > 0.05). HSS scores and knee ROM in the HROM group were significantly higher than those in the control group 1 and 2 months after surgery (P < 0.001). There were no significant differences in VAS at 1, 2 and 7 days after surgery between the two groups. The usage of analgesic drugs, wound complications, thrombus of lower limb, and transfusion rates were similar between the two groups (P > 0.05). Conclusions High knee ROM at discharge achieved through high-intensity rehabilitation is an effective and simple way to improve early knee mobility and function. The routine application of this protocol did not increase the incidence of wound complications.